Household perceptions regarding bats and willingness to pay for their conservation within Mount Elgon Biosphere Reserve of Uganda - Siya, Aggrey; Rwego, Innocent B.; Sande, Eric; Kityo, Robert M.; Masembe, Charles; Kading, Rebekah C. (Frontiers in Conservation Science, 2025)
IntroductionBats play critical roles not only in sustaining ecosystems but also human livelihoods across different scales. Despite such values, their populations continue to be threatened mainly by human activities causing their decline. Moreover, recent zoonotic diseases outbreaks have increased negative attitudes towards this taxon further threatening their populations. This study sought to contribute to bat conservation programs by providing scientific data on community willingness to pay for bat conservation within Mount Elgon Biosphere Reserve in Uganda.MethodsWe employed cross-sectional survey design using semi structured interview questionnaires to gather data on the willingness to pay for bat conservation as well as factors associated within Mount Elgon Biosphere Reserve of Uganda. Households were the unit of analysis and were sampled using simple random sampling techniques. Data collected was analyzed using descriptive and relational analyses.ResultsRespondents indicated their willingness to contribute a mean monetary value of UgX 794.97 (~ USD 0.21 Oanda rates as of September 03rd, 2024). This bid amount was associated with household size (p = 0.02) and lower education levels (p = 0.01). Increased household size as well as higher education levels undermined willingness to pay for conservation of bats. Gender and years lived in the area had a positive effect on willingness to pay for bat conservation. In terms of knowledge of bats, this study indicated understanding of some aspects of bats e.g., role in pollination and reproduction. However, there was poor knowledge on other aspects e.g., seed dispersion and other ecological values. Regarding the general environment, communities indicated environment to play critical roles in their livelihoods and ought to be protected.DiscussionHuman communities within Mount Elgon have positive attitudes towards bats and are willing to contribute to their conservation, including monetary terms. Interventions targeting bat conservation thus ought to integrate human dimensions. This will contribute to restoring bat populations and local, regional and global scales.